Kenya : the essential guide to customs & culture - Barsby, Jane (London, England : Kuperard, 2017)
"Culture Smart! Kenya provides a cultural bridge that will carry you beyond the gloss of the hotels and deep into the warp and weft of everyday life; beyond the game parks and into the intricacies of community and wildlife coexistence; beyond the bounds of tourism and into the freedom of cultural understanding and exchange. A true "insider's take" gleaned over years of living and working in the country, it delivers key insights into the forces, ancient and modern, that have shaped Kenya--and practical guidance on how best to enter into the modern Kenyan business and social environment. Named after snow-capped Mount Kenya, the second-highest mountain in Africa, Kenya is fringed by the silver-blue strand of the Indian Ocean, studded with flamingo-flecked lakes, swathed in rolling savannah, and embraced by the last of the primordial rain forests. Stunningly scenic, steeped in history, a sportsman's paradise, and a lover's idyll, for over a century Kenya was a playground for royalty, millionaires, aristocrats, and eccentrics. Today, thanks to its high-action pursuits, cultural treasures, wealth of wildlife, and glorious beach life, it remains one of the world's most popular tourist destinations, and the unrivaled "safari capital of the world." As to its people, Kenya is a cultural microcosm comprising more than seventy ethnic groups. Each has its own distinctive cultural identity, ranging from the red-cloaked hauteur of the Maasai to the heady coastal cocktail of the Swahili people. All extend the warmth of welcome that has proved to be Kenya's most valuable asset to tourism"--Publisher
Subtitle from cover.
Edition statement and copyright are on page 165.
Includes bibliographical references and index.
Keywords: Etiquette -- Kenya -- Handbooks, manuals, etc; National characteristics, Kenyan -- Handbooks, manuals, etc; Visitors, Foreign -- Kenya -- Life skills guides; Manners and customs